1986
DOI: 10.1111/j.1399-3054.1986.tb05955.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inhibition of French‐bean and soybean nitrogen fixation by nitrate, 1% oxygen or direct assimilate deprivation

Abstract: Inhibition by NO−3 of acetylene reduction in bean (Phaseolus vulgaris L. cv. Contender) and soybean (Glycine max L. cv. Amsoy 71) was measured in parallel with nodule carbohydrate and nitrate metabolism. In bean the onset of inhibition of C2H2 reduction (6 h) coincided with decreased import of assimilates and a lowering of carbohydrate pools (sucrose, glucose and starch). Nitrate reductase (EC 1.6.6.1) activity was induced in all plant organs after 3 h but no nitrite was detected in the nodules. In soybean, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
4
37
1
Order By: Relevance
“…In the period from 3 to 26 h after girdling, the soluble sugar levels were relatively stable, but the starch pools continued to decline to 47 and 54% of the initial pool sizes in nodule and roots, respectively. These results are similar to those reported in a recent study (25) (26) increased photosynthesis by increasing the pCO2 surrounding the leaves and found that nodule specific activity was not affected. Since leaf starch pools accumulate at a rate such that export rates from the leaf are constant under high pCO2 (8), it may be concluded, again, that translocation rate is limiting nodule activity.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…In the period from 3 to 26 h after girdling, the soluble sugar levels were relatively stable, but the starch pools continued to decline to 47 and 54% of the initial pool sizes in nodule and roots, respectively. These results are similar to those reported in a recent study (25) (26) increased photosynthesis by increasing the pCO2 surrounding the leaves and found that nodule specific activity was not affected. Since leaf starch pools accumulate at a rate such that export rates from the leaf are constant under high pCO2 (8), it may be concluded, again, that translocation rate is limiting nodule activity.…”
supporting
confidence: 82%
“…3), the absolute size of these pools cannot be used as a reliable indicator of the carbohydrate limitation of the nodule. Previous workers (17,22,25) have claimed that nodules are not carbohydrate limited, since carbohydrate reserves remained in the nodule under conditions in which nodule activity was declining. These studies have not considered the size of the nodule starch/sucrose pool relative to the nodule respiratory need, the distribution of these reserves between nodule cortical, infected and uninfected cells, or the possibility that nodule starch reserves might not be mobilized at a rate sufficient to maintain maximal rates ofnodule metabolism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…activity and nodule carbohydrate levels were observed after shoot excision in French bean (22), defoliation of clover (3), and stem girdling of soybean (21). The organic acids succinate and fumarate were most effective in stimulating ARA, although neither of the substrates completely prevented the decline in ARA with time (Table I).…”
Section: Discussionmentioning
confidence: 97%